2016
DOI: 10.1038/srep24838
|View full text |Cite
|
Sign up to set email alerts
|

Microbial metabolite butyrate facilitates M2 macrophage polarization and function

Abstract: Metabolites from intestinal microbes modulate the mucosal immune system by regulating the polarization and expansion of T cells. Whether the microbial metabolites influence macrophage polarization, however, is poorly understood. Here, we show that the large bowel microbial fermentation product, butyrate, facilitates M2 macrophage polarization, in vitro and in vivo. The supernatant from butyrate-treated M2 macrophage increased the migration and enhanced the wound closure rate of MLE-12 cells. Butyrate attenuate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
180
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(194 citation statements)
references
References 43 publications
11
180
3
Order By: Relevance
“…These genes, among others, were also downregulated in macrophages from antibiotic-treated mice, and exhibited impaired interferon signaling and anti-viral function compared to conventionally-housed mice [33]. Recent work also demonstrated a novel role for butyrate in facilitating colitis-protective M2 macrophage polarization in vivo , as well as reducing TNF-α and IL-1β production to suppress inflammation [34]. Moreover, in vitro experiments on bone marrow-derived macrophages indicated that M0 to M2 differentiation was induced by butyrate, potentially through inhibition of HDACs and enhanced histone H3K9 acetylation and Il-4/STAT4 signaling [34].…”
Section: Epigenomic Mechanisms Regulate Microbiota-dependent Immune Hmentioning
confidence: 99%
See 1 more Smart Citation
“…These genes, among others, were also downregulated in macrophages from antibiotic-treated mice, and exhibited impaired interferon signaling and anti-viral function compared to conventionally-housed mice [33]. Recent work also demonstrated a novel role for butyrate in facilitating colitis-protective M2 macrophage polarization in vivo , as well as reducing TNF-α and IL-1β production to suppress inflammation [34]. Moreover, in vitro experiments on bone marrow-derived macrophages indicated that M0 to M2 differentiation was induced by butyrate, potentially through inhibition of HDACs and enhanced histone H3K9 acetylation and Il-4/STAT4 signaling [34].…”
Section: Epigenomic Mechanisms Regulate Microbiota-dependent Immune Hmentioning
confidence: 99%
“…Recent work also demonstrated a novel role for butyrate in facilitating colitis-protective M2 macrophage polarization in vivo , as well as reducing TNF-α and IL-1β production to suppress inflammation [34]. Moreover, in vitro experiments on bone marrow-derived macrophages indicated that M0 to M2 differentiation was induced by butyrate, potentially through inhibition of HDACs and enhanced histone H3K9 acetylation and Il-4/STAT4 signaling [34]. Importantly, decreased gene expression in response to butyrate is not consistent with the generally expected outcome of HDAC inhibition and increased histone acetylation, indicating that butyrate is possibly functioning through other mechanisms in addition to HDACs or that butyrate-induced increased histone acetylation at specific genes mediates decreased gene expression.…”
Section: Epigenomic Mechanisms Regulate Microbiota-dependent Immune Hmentioning
confidence: 99%
“…Interestingly, anti-inflammatory effects of butyrate are independent of TLR signaling and are mediated by inhibition of histone deacetylases (HDACs)(139). In addition to suppressing pro-inflammatory response by activated myeloid cells, SCFAs can also facilitate M2 polarization of macrophages by directly activating STAT6 signaling(141). Whether SCFAs can influence innate control of T cell responses has not been directly tested however, butyrate-producing Clostridia was shown to attenuate GVHD(142), a disease with a strong T cell component.…”
Section: Introductionmentioning
confidence: 99%
“…Present study reveals the key to understand how an in-vitro-of lumen pH and to exert many beneficial extra-intestinal effects through epigenetic mechanisms [15] . Ji J. group showed that the large bowel microbial fermentation product, butyrate, facilitates M2 macrophage polarization, in vitro and in vivo [16] . Chang PV.…”
Section: Resultsmentioning
confidence: 99%